Aptamer-based detection of foot-and-mouth disease virus using single-stranded DNA probe - Nordin, Nor Aina; Soon, Samson; Senawi, Jamaliah B.; Jinin, Zurin Azlin M.; Arshad, Siti Suri; Abd Rahaman, Yasmin; Azri, Farah Asilah (Springer, 2024)
Foot-and-mouth disease (FMD) is known for its highly contagious properties among cloven-hoofed animals resulting in significant morbidity rates. Incursions of this disease have caused significant losses in affected countries in Southeast Asia and Africa, even within EU countries which resulted in significant financial losses. This study is aimed at addressing existing limitations by creating a diagnostic method using aptamer-based assay. Three DNA aptamers were engineered to target the VP2 region of the FMD viral capsid protein. Since VP2 demonstrates a highly conserved amino acid sequence across serotypes, the specifically designed aptamers can detect different serotypes of the virus. Aptamers were evaluated against VP2 capsid protein, which was synthesized based on sequences from serotypes A, O, and Asia 1 of the FMD virus. After the recombinant VP2 capsid protein was developed, expressed, and refined, it was applied using enzyme-linked aptamer sorbent assay (ELASA) to determine aptamers’ binding capability. A similar test was further conducted with purified FMD virus from serotype A and serotype O. The ELASA results displayed a notable sensitivity in identifying the FMDV. Under optimized conditions, the aptamers have LOD as low as 0.11 ng/mL with LOQ as low as 0.34 ng/mL. The binding strength analyzed using the equilibrium dissociation constant (Kd) showed strong binding affinity at 3.092 ± 0.05 nM. Based on these findings, the method shows significant potential with high sensitivity and specificity for FMD virus detection assay.